Method of Allama Abul Fazl Al Borqaee (d 1413 H) in his Tafseer "Tabeshe az Quran" - Heravi, Sayed jamal ud Din (QiST: Journal of Quran and Tafseer Studies, 2024)
The Quran, the cornerstone of Islam, underpins the faith, society, and civilization of the Muslim world. As the final divine revelation bestowed upon Prophet Muhammad (SAW), it was his duty to memorize and convey its teachings to his companions. This responsibility extends to the entire Muslim community, especially the ulamas (Islamic scholars), as the Prophet (SAW) emphasized the importance of learning and teaching the Quran. Through the dedicated efforts of ulamas, the Quran has been preserved from any alterations, fulfilling Allah's promise of protection. This research focuses on the translation methodology of Allama Burqaee, a distinguished Persian translator of the Quran. The significance of this study lies in recognizing Allama Burqaee's outstanding contributions to Islamic scholarship. He authored over a hundred works, including translations of the Quran and Hadith, and conducted extensive research on various religions and conflicting beliefs. His tafseer (exegesis) is particularly valuable for students of Islamic studies due to its comprehensive integration of Sunni and Shia scholarly perspectives and ease of access to primary sources. The choice of this topic is motivated by several reasons: (1) To acknowledge Allama Burqaee's efforts in opposing religious innovations (bida'). (2) To understand Allama Burqaee's approach to the Quran, Sunnah, and other Islamic sciences. (3) To highlight his inclusion of diverse scholarly opinions and contemporary ijtihad (intellectual striving). (4) To elucidate his emphasis on the importance of aqeeda (belief), a foundational aspect of Islam. (5) To discuss his call for Muslim unity based on the Quran and Sunnah. The research methodology involves following Allama Burqaee's approach without alterations, providing explanations and critical commentary when necessary. The steps include examining Quranic verses with references, analyzing Hadith and athar (traditions) from primary sources, considering scholarly consensus, and offering concise definitions and examples. This study aims to present a thorough understanding of Allama Burqaee's translation methods and their implications for Islamic scholarship.